Treponema pallidum Disrupts VE-Cadherin Intercellular Junctions and Traverses Endothelial Barriers Using a Cholesterol-Dependent Mechanism - Lithgow, Karen V.; Tsao, Emily; Schovanek, Ethan; Gomez, Alloysius; Swayne, Leigh Anne; Cameron, Caroline E. (Frontiers in Microbiology, 2021)
Treponema pallidum subspecies pallidum, the causative agent of syphilis, traverses the vascular endothelium to gain access to underlying tissue sites. Herein, we investigate the mechanisms associated with T. pallidum traversal of endothelial barriers. Immunofluorescence microscopy reveals that a subpopulation of T. pallidum localizes to intercellular junctions and that viable T. pallidum, as well as a T. pallidum vascular adhesin (Tp0751), disrupts the architecture of the main endothelial junctional protein VE-cadherin. Intriguingly, in this study we show that T. pallidum traverses endothelial barriers with no disruption in barrier permeability. Furthermore, barrier traversal by T. pallidum is reduced by pretreatment of endothelial cells with filipin, an inhibitor that blocks cholesterol-mediated endocytosis. Collectively, these results suggest that T. pallidum can use a cholesterol-dependent, lipid raft-mediated endocytosis mechanism to traverse endothelial barriers. Further, treponemal localization to, and disruption of, intercellular junctions suggests that a paracellular route may also be utilized, a dual traversal strategy that has also been observed to occur for leukocytes and other invasive bacteria.